Hubungan faktor-faktor pelan penggantian dengan penerusan kepimpinan cemerlang - Salleh, Maimunah (2010)
The aim of this research is to identify the level of each SP factors; dominant criteria’s of excellent leadership and also the relationship of each SP factors with excellent leadership criteria’s. There are 108 administration officers in Gred N41, N44 and N48 in UTM Skudai and International Campus were involved as respondents. Research data was collected through questionnaires which was built by Rothwell (2001) to measure SP factors and was built IBHR Consulting Sdn. Bhd. (2006) to measure excellent leadership. Data obtained were analyzed using descriptive and inferential (Pearson correlation) statistics. The result showed the highest result in the level of each SP factors within UTM’s administration officers. The findings shown the relationship, integrity and change were the dominant criterion. Through correlation test, the result showed there was a significant correlation of each SP factors with majority excellent leadership criteria’s, except integrity. In this research, suggestions for future studies and recommendations for positive actions to be taken by organization were also suggested.